Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. Also use ^ to indicate powers (eg x-squared = x^2).

Q: What is the answer to 1y 4 3y - 5 2y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5 - 2y = 3y - 5 10 = 5y So, y = 2.

80 = 3y + 2y + 4 + 1 80 = 5y + 5 80 - 5 = 5y + 5 - 5 75 = 5y 75 / 5 = 5y / 5 15 = y

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

5+y+2y? = 5+3y?

This is a system of equations, and we can use various methods to solve it. We'll use substitution in this case. We're told: 2x + 3y = -5 5x + 2y = 4 To solve by substitution, what we need to do is take either one of those equations, and solve it for either x or y. Let's take the second one and solve it for x: 5x + 2y = 4 5x = 4 - 2y x = (4 - 2y)/5 Now we can take that solution for x, and substitute it into the other equation: 2x + 3y = -5 2((4 - 2y)/5) + 3y = -5 (8 - 4y) / 5 + 3y = -5 (8 - 4y + 15y) / 5 = -5 8 - 4y + 15y = -25 11y = -33 y = -3 We now have a value for y, and can plug it into either of the original equations to solve for x: 2x + 3y = -5 2x + 3(-3) = -5 2x - 9 = -5 2x = 4 x = 2 To verify our answer, we can plug either x or y into the other of our original equations, and see if we get the same result for the other variable: 5x + 2y = 4 5(2) + 2y = 4 10 + 2y = 4 2y = -6 y = -3 So that confirms our answer, and the two equations intersect at the point (2, -3).

Related questions

5y + (4 - 2y) = 9 5y + 4 - 2y = 9 3y + 4 = 9 3y = 5 y = 5/3

5 - 2y = -3y - 2Subtract 5 from each side:-2y = -3y - 7Add 3y to each side:y = -7

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8

5 - 2y = 3y - 5 10 = 5y So, y = 2.

3y + 2y + 4 + 1 = 805y + 5 = 805y = 75y = 15

2y + 1.

I don't know whether it's y^2-3y+2+3y-4y-5 or 2y-3y+2+3y-4y-5, so I'll do both.y^2-3y+2+3y-4y-5y^2+(-3y+3y-4y)+(2-5); group them togethery^2+(-4y)+(-3)y2-4y-3OR2y-3y+2+3y-4y-5(2y-3y+3y-4y)+(2-5); group them together(-2y)+(-3)-2y-3

3y+2y+4+1=80 5y+5=80 5y=80-5 5y=75 y=15

If you mean: 80 = 3y+2y+4+1 then 80 =5y+5 and so y = 15

80 = 3y + 2y + 4 + 1 80 = 5y + 5 80 - 5 = 5y + 5 - 5 75 = 5y 75 / 5 = 5y / 5 15 = y

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

x + y = 1 x + y = 2 x + 2y = 2 x + 3y = 3 2x + 3y = 4 2x + 5y = 5 x - 2y = 2 x - 3y = 3 2x - 3y = 4 a + b + 2c + 3d +e -6f + 2x - 5y = 5